2017
DOI: 10.1007/s11882-017-0747-5
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Cigarettes: Their Constituents and Potential Links to Asthma

Abstract: Purpose of Review Vaping is gaining popularity in the USA, particularly among teens and young adults. While e-cigs are commonly represented as safer alternatives to tobacco cigarettes, little is known regarding the health effects of their short- or long-term use, especially in individuals with pre-existing respiratory diseases such as asthma. Flavored e-cig liquids (e-liquids) and e-cig aerosols contain airway irritants and toxicants that have been implicated in the pathogenesis and worsening of lung diseases.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
160
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(173 citation statements)
references
References 121 publications
4
160
0
9
Order By: Relevance
“…Evidence indicates that e-cigarette vapor can produce oxidative stress and inflammation in airways and may exacerbate or induce rhinitis, asthma, eczema, and allergic symptoms (173). Epidemiologic investigations found increased e-cigarette use among asthmatics (174,175) and associations between e-cigarette use and increased asthma (176) and asthma attack (175) prevalence. Exposure to nicotine-containing e-liquid in "asthmatic" mice increased airway eosinophils, Th2 cytokines, and AHR (172,177).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence indicates that e-cigarette vapor can produce oxidative stress and inflammation in airways and may exacerbate or induce rhinitis, asthma, eczema, and allergic symptoms (173). Epidemiologic investigations found increased e-cigarette use among asthmatics (174,175) and associations between e-cigarette use and increased asthma (176) and asthma attack (175) prevalence. Exposure to nicotine-containing e-liquid in "asthmatic" mice increased airway eosinophils, Th2 cytokines, and AHR (172,177).…”
Section: Resultsmentioning
confidence: 99%
“…Exposure to nicotine-containing e-liquid in "asthmatic" mice increased airway eosinophils, Th2 cytokines, and AHR (172,177). The toxicity of components unique to e-cigarettes likely induces unique respiratory and possibly allergic effects and warrants further investigation (172,174).…”
Section: Resultsmentioning
confidence: 99%
“…These animal studies suggest that in our murine model, exposure to VEA and cartridges has promoted allergic asthmarelated in ammation-causing lung injury, especially in VEA exposed mice. However, it may be possible that these lower LTC4 levels seen in the cartridge exposed group may be confounded by the presence of nicotine as nicotine has LTC4 suppressive effects [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…[49][50][51] This association was documented in two independent surveys carried out among teenage electronic cigarette users with a risk of bronchitis symptoms directly related to the frequency of electronic cigarette usage. 46,52,53 Detrimental acute effects of electronic cigarettes inhalation were demonstrated in a study conducted by Antoniewicz et al among 17 healthy individuals, which showed that inhaled electronic cigarette aerosol with nicotine caused a significant increase in heart rate and arterial stiffness, and a sharp increase in flow resistance in the conducting airways. 54 Similarly, acute vaping of propylene glycol/ glycerol aerosol at high wattage with or without nicotine induced significant injury to airway epithelium and impaired pulmonary gas exchange.…”
Section: Potential Health Harms Of Electronic Cigarettes Unrelated Tomentioning
confidence: 99%